Fuel cell model for three-phase inverter - Younis, M.A.A.; Rahim, N.A.; Mekhilef, Saad (2006)
This paper presents a fuel cell model supplying three-phase dc/ac inverter. Simulink used as interactive tool to model the proposed fuel cell system. The fuel cell output voltage is proportional to the change of the air (oxidant) pressure, the hydrogen (fuel) pressure and the current withdrawn from the fuel cell. Three-phase dc/ac inverter used to supply the ac load. Symmetric Space Vector Pulse Width Modulation used to drive the three-phase inverter so that minimum harmonic distortion on the load side voltage and current. Simulation results provided to validate the design.